2018
DOI: 10.1177/1060028018777547
|View full text |Cite
|
Sign up to set email alerts
|

Quality Use of the Pathology Data in Home Medicines Reviews: A Retrospective Evaluation

Abstract: In total, 580 reports were evaluated. Of these, 179 reports did not contain any pathology data. Pharmacists commented on provided laboratory values in 324 reports and recommended further testing in 473 reports. Not all suggestions were related to previous values or were in line with guidelines. Most recommendations were regarding vitamin D and lipids (69% and 62% of medication review reports, respectively). Particularly, regarding renal impairment, pharmacists used their knowledge on dose adjustments and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It has been shown that a general practice pharmacist is effective at improving the timeliness of completion of Home Medicine Reviews (HMR) [ 39 ]. A complete HMR service includes the service provided by a GP, an accredited pharmacist (a pharmacist who is licensed to conduct medication management reviews, including HMRs and Residential Medicine Management Reviews (RMMR)), and input from a multidisciplinary team from the time the patient is identified through to the implementation and ongoing monitoring of the medication management plan and any follow-up service(s) as required [ 72 ]. In 2012, Freeman et al reported that a general practice pharmacist completed HMRs in a shorter time (within 20 days) than an accredited pharmacist who is external to general practice (within 56 days) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that a general practice pharmacist is effective at improving the timeliness of completion of Home Medicine Reviews (HMR) [ 39 ]. A complete HMR service includes the service provided by a GP, an accredited pharmacist (a pharmacist who is licensed to conduct medication management reviews, including HMRs and Residential Medicine Management Reviews (RMMR)), and input from a multidisciplinary team from the time the patient is identified through to the implementation and ongoing monitoring of the medication management plan and any follow-up service(s) as required [ 72 ]. In 2012, Freeman et al reported that a general practice pharmacist completed HMRs in a shorter time (within 20 days) than an accredited pharmacist who is external to general practice (within 56 days) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…27 Even though pharmacists' recommendations in HMR reports are evidence-based, 28 they are not reported in a standardized manner and may not routinely include the rationale or adequate evidence for recommendations. 29 GPs are more likely to accept pharmacist recommendations when the medication review is collaborative with discussions about the patient and specific findings, 27 as the program actually requires.…”
Section: Barriers To Hmrsmentioning
confidence: 99%
“…Despite medication reviews being extensively utilised in Australia and in other parts of the world for over 20 years, current literature on medication reviews mainly focuses on the impact a pharmacist has on direct or surrogate health outcomes with varying results [17,21]. Surrogate outcomes include identifying medication-related problems and the recommendations made as a result, and the perceptions of consumers and GPs toward the medication review process [17,21,[23][24][25][26][27][28][29][30][31][32][33]. Other retrospective studies have evaluated the types of medication-related problems identi ed, the prevalence of their identi cation, and the subsequent acceptance and implementation of medicines review pharmacist recommendations by the GPs [10,15,17,28].…”
Section: Introductionmentioning
confidence: 99%